Pengaruh Rasio Keuangan dan Earning per Share terhadap Harga Saham Perusahaan Sektor Finansial di Bursa Efek Indonesia Periode 2021–2023 - Ellynawati Ellynawati; Tuti Achyani; David Chandrawan; Anna Fajarwaty; Ayu Ambarwati; Shakira Sitirouloh Tuanaya (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effect of financial ratios and earnings per share on stock prices of financial sector companies listed on the Indonesia Stock Exchange during 2021–2023. Using a quantitative explanatory design with panel data regression, the sample consists of firms selected through purposive sampling based on data completeness and consistency. The independent variables include return on assets, return on equity, net profit margin, and earnings per share, while stock price is measured by annual closing price. The results indicate that earnings per share demonstrates the strongest and most consistent positive influence on stock prices, while profitability ratios show varying levels of significance across models. Simultaneous testing confirms that all variables jointly affect stock prices, and model evaluation suggests that the fixed effect specification provides the best fit with satisfactory explanatory power. These findings support signaling theory and fundamental analysis, emphasizing the importance of financial performance indicators in investor decision making.